2017
DOI: 10.1002/celc.201700376
|View full text |Cite
|
Sign up to set email alerts
|

Modification Based on MoO3 as Electrocatalysts for High Power Density Vanadium Redox Flow Batteries

Abstract: Molybdenum oxide MoO3 has been widely used in catalysts and electrochemical energy devices, but, to date, has not been investigated as an electrocatalyst in redox flow cells. In this study, MoO3 in the form of micro‐flakes was introduced onto carbon paper as an electrocatalyst and MoO42− as electrolyte additive for the vanadium redox couple reactions in the vanadium redox flow battery (VRFB). When the carbon paper was modified with MoO3 or MoO42− added to the electrolyte, the peak potential separations were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Mn 2 + , Te 4 + and In 3 + exhibited similar enhancement in the electroactivity but Pt, Pd and Au salts were found to catalyse the hydrogen evolution which will decrease the coulombic efficiency of the VRFBs. Recently, Cao et al reported that adding MoO 4 2 − into the electrolyte can achieve a similar improvement as that involving the modification of carbon paper electrodes with MoO 3 , leading to an increase in the cell voltage efficiency by more than 5% over the current density range 100-150 mA cm −2 [80] .…”
Section: Kinetic Enhancersmentioning
confidence: 97%
“…Mn 2 + , Te 4 + and In 3 + exhibited similar enhancement in the electroactivity but Pt, Pd and Au salts were found to catalyse the hydrogen evolution which will decrease the coulombic efficiency of the VRFBs. Recently, Cao et al reported that adding MoO 4 2 − into the electrolyte can achieve a similar improvement as that involving the modification of carbon paper electrodes with MoO 3 , leading to an increase in the cell voltage efficiency by more than 5% over the current density range 100-150 mA cm −2 [80] .…”
Section: Kinetic Enhancersmentioning
confidence: 97%
“…Cao et al prepared MoO3 deposits on carbon paper and examined the activity of this electrode material for both the positive 2+ + 2 VO /VO and the negative V 2+ /V 3+ electrode reactions [421]; as an alternative approach, the effects of added [2][3][4] MoO in the electrolyte solutions was examined. Smaller peak potential separations were found.…”
Section: Metal Oxide Depositsmentioning
confidence: 99%
“…This was responsible for the improvement of voltage efficiency of the VRFB cell. In one study 57 , it was also shown that addition of 5 mM of Na2MoO4 directly to the electrolytes modified the surface of the electrodes during cycling and produced similar effects on VRFB cell performance as MoO3 deposited on electrodes. In our experiments, the deposition of molybdenum compounds after cycling was not observed, and the dissolved molybdenum appeared to slightly worsen the reversibility of redox couples, though not seriously.…”
Section: Vrfb Single Cell Performancementioning
confidence: 96%